Improving PAI Learning Implementation Of Artificial Intelligence (AI) Based Question Generation Selection In Improving PAI Learning: Implementation Of Artificial Intelligence (AI) Based Question Generation Selection In Improving PAI Learning - Annisa Aulia Evinda; Salsa Syafa Rizkyna; Indah Aminatuz Zuhriyah (STAI Terpadu Yogyakarta, 2025)
The purpose of this research is to implement the creation of multiple choice questions using Artificial Intelligence (AI) to improve Islamic Religious Education (PAI) learning. The discussion in this article takes several references to previous research with a variety of uses and benefits in making multiple choice questions with the use of artificial intelligence. The research method uses literature review by selecting references using international and national articles and books to strengthen the research of this article. The results of this study with various previous studies found that the need for strategy and selection of multiple choice questions adjusts the learning context. With the flow of the context of achieving learning effectiveness in the form of strategy, planning, implementation and evaluation as well as the selection of multiple choice questions by taking several references universally and deeply, the success of a learning process between students and students, or students and teachers in achieving learning goals